Some Reasons of Using Native Language as Medium of Instruction at Non-English Department - Sri Sukarni; Tri Setianingsih; Terasne Terasne (Humanitatis : Journal of Language and Literature, 2020)
This research aimed to describe the reasons of using Indonesian language as medium of instruction at non-English department students. This research is conducted at non English department of Mandalika University of Education and there were two English general lecturers and 14 students taken as samples. Type of research used in this research was descriptive quantitative research by survey model. Data were taken from the result of questionnaires answered by both lecturers and students then analyzed by using frequency and percentage. Based on the research findings it can be concluded that there were ten reasons of using Indonesian as medium of instruction for non-English department students. Those ten reasons covered three functions that for teaching language skills, teaching the component of language skills and class management. The three functions gave positive effect in teaching and learning English at non-English department. For teaching language skills aimed to develop students’ understanding in reading comprehension, to discuss among students is easier, and to make English easy to learn. The using of Indonesian in component of language skills aimed to explain difficult words in reading text in students’ native language, to explain grammar, to explain error made by the students. The reasons of using Indonesian in classroom management can be seen before and after teaching and learning process such as to explain new English teaching material, to develop learning atmosphere more comfortable, to ensure understanding of previous teaching material and giving instruction for assignment or test.